Developing an Integrated Model of Creative Economy and Halal Tourism in Aceh Tengah: An Analytic Network Process Approach - Syaripuddin Syaripuddin; Harley Agustian; Zahara Zahara (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study is situated within the growing importance of creative economy and halal tourism as interconnected drivers of inclusive regional development, particularly in Muslim-majority contexts such as Aceh Tengah Regency. The research aims to examine stakeholder synergy in developing these sectors by identifying key challenges, strategic solutions, and implementation priorities from the perspectives of government, academics, and entrepreneurs. A qualitative approach was employed through expert interviews, supported by the Analytic Network Process (ANP) framework using Super Decisions software to structure and prioritize strategic indicators based on expert judgments. The findings reveal four essential pillars for development: improved accessibility, strengthened creative human resources, enhanced digital marketing, and environmental sustainability. Accessibility emerges as a foundational factor influencing connectivity, economic participation, and regional competitiveness, while human resource development is central to fostering innovation and long-term sector resilience. Digital marketing expands market reach and strengthens halal-oriented promotional strategies, whereas environmental sustainability ensures balance between economic growth, ecological preservation, and social well-being. The study further conceptualizes development through two interlinked pillars: infrastructure and creative ecosystem strengthening, and sustainability with inclusivity integration. These findings imply the need for coordinated policy frameworks that align economic development with Islamic values, local cultural identity, and sustainable growth principles in Aceh Tengah. ABSTRAK - Pengembangan Model Terintegrasi Ekonomi Kreatif dan Pariwisata Halal di Aceh Tengah: Pendekatan Analytic Network Process. Kajian ini berangkat dari semakin pentingnya ekonomi kreatif dan pariwisata halal sebagai dua sektor yang saling terhubung dalam mendorong pembangunan daerah yang inklusif, khususnya di Kabupaten Aceh Tengah. Penelitian ini bertujuan untuk menganalisis sinergi para pemangku kepentingan dalam pengembangan kedua sektor tersebut melalui identifikasi tantangan utama, solusi strategis, serta prioritas implementasi berdasarkan perspektif pemerintah, akademisi, dan pelaku usaha. Pendekatan yang digunakan adalah kualitatif melalui wawancara mendalam dengan para ahli, yang kemudian dipadukan dengan kerangka Analytic Network Process (ANP) menggunakan perangkat lunak Super Decisions untuk menyusun dan menentukan prioritas strategi berdasarkan penilaian ahli. Hasil penelitian menunjukkan empat pilar utama pengembangan, yaitu peningkatan aksesibilitas, penguatan sumber daya manusia kreatif, pengembangan digitalisasi pemasaran, serta pelestarian lingkungan. Aksesibilitas menjadi faktor dasar dalam memperkuat konektivitas, meningkatkan partisipasi ekonomi masyarakat, dan daya saing daerah. Sementara itu, penguatan sumber daya manusia berperan penting dalam mendorong inovasi dan keberlanjutan sektor, sedangkan digitalisasi pemasaran membuka perluasan pasar dan memperkuat promosi berbasis nilai-nilai halal. Pelestarian lingkungan menjadi aspek penting dalam menjaga keseimbangan antara pertumbuhan ekonomi, kelestarian alam, dan keberlanjutan sosial. Secara konseptual, pengembangan diarahkan pada dua pilar utama, yaitu penguatan infrastruktur dan ekosistem kreatif serta integrasi prinsip keberlanjutan dan inklusivitas, yang diharapkan membentuk model pembangunan yang inovatif, berkeadilan, dan berdaya saing.